1994
DOI: 10.1016/0257-8972(94)90091-4
|View full text |Cite
|
Sign up to set email alerts
|

Properties of alumina films prepared by atmospheric pressure metal-organic chemical vapour deposition

Abstract: Thin alumina films were deposited at low temperatures (290-420 °C) on stainless steel, type AISI 304. The deposition process was carried out in nitrogen by metal organic chemical vapour deposition using aluminium tri-sec-butoxide. The film properties including the protection of the underlying substrate against high temperature corrosion, the chemical composition of the film, the microstructure, and the refractive index were investigated. The activation energy for the heterogeneous reaction was 83 _+ 5 kJ mol ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
7
15
1
Order By: Relevance
“…7 shows the AES depth profile of the sample with a thickness of about 0.6 gm; the peak-to-peak height is shown as a function of the sputter depth. This corresponds well with earlier experiments [ 15,16] which showed that alumina films deposited in a nitrogen atmosphere also did not contain any carbon. FTIR was used to identify functional groups such as H-O and A1-O groups.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…7 shows the AES depth profile of the sample with a thickness of about 0.6 gm; the peak-to-peak height is shown as a function of the sputter depth. This corresponds well with earlier experiments [ 15,16] which showed that alumina films deposited in a nitrogen atmosphere also did not contain any carbon. FTIR was used to identify functional groups such as H-O and A1-O groups.…”
Section: Resultssupporting
confidence: 79%
“…The refractive indices were measured with a Plasmos ellipsometer and are shown in refractive index is given as a function of the water concentration, and changes from 1.56 to 1.63 when the water concentration changed from 0 to 0,017kPa, which corresponds well with the value for amorphous alumina [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations